PERAN PROJECT MANAGER DAN INSIGHT EXECUTIVE DALAM BRAND COMMUNICATION “BERCERITA DI BU LURAH” SEBAGAI UPAYA PENGUATAN BRAND IMAGE KOPI SUSU BU LURAH SEMARANG - Benedictus Bimo; Yanuar Luqman (Interaksi Online, 2026)
Kopi Susu Bu Lurah Semarang faces a gap between its brand philosophy of emotional closeness and the perception of coffee shop goers aged 18–35 in Semarang, who still associate the brand with functional traits such as friendliness and efficiency. The “Bercerita di Bu Lurah” campaign was implemented to align its brand image with this philosophy while delivering consumer benefits. The campaign used the AIDA structure with content marketing, advertising, media coverage, influencer marketing, direct marketing and event marketing, supported by gamification in sales promotion. The results show a decrease in the functional dimension by -4.57% and an increase in the emotional dimension by +21.59%. The campaign also retained 34 friendship groups as loyal visitors and achieved 1,685,557 impressions and 791,650 accounts reached on Instagram. Overall, the campaign successfully strengthened the brand image as an emotionally close coffee shop with meaningful consumer benefits.